Využití telemedicíny v arytmologii - Bulková, Veronika; Pindor, Jakub; Plešinger, Filip; Viščora, Ivo; Fiala, Martin (Vnitrni lekarstvi, 2022)
Telemedicine can be defined as a health care service that, specifically in the field of diagnostics, employs remote transfer of a large volume of data from a large number of subjects at the same time. This data is subsequently processed on a central basis and returned to a large number of health care providers by whom the service was ordered on national or international level. In arrhythmology, telemedicine is used particularly in long-term ECG monitoring to diagnose arrhythmias and check out treatment outcome via external recorders, smart watch, and implantable devices. To facilitate analysis of large telemedicine data volume, artificial intelligence is being increasingly exploited.
Keywords: defibrilátory implantabilní; kardiostimulátor; artificial intelligence; Artificial Intelligence; Telemedicine; umělá inteligence; telemedicína; Arrhythmias, Cardiac; ECG monitoring; Humans; telemedicine; Defibrillators, Implantable; lidé; arrhythmology; Pacemaker, Artificial; srdeční arytmie